Improvement of the business banking credit process through the application of lean thinking in a medium-scale banking institution - Geronimo Cier, Alonso Martin (2024)
In a society in constant growth, banking institutions have been forced to satisfy more and more the needs of their clients. Among the most requested services are the bank loans, particularly those intended for medium and large-sized companies. This study deals with the development of a proposal to improve the evaluation stage of the business banking credit process, this stage has a duration of 12 days, generating cost overruns and multiple sources of waste. The implementation of Lean thinking, Business process management and the use of simulation will be used to achieve the objectives. The results obtained were as expected, demonstrating that by implementing different improvements in certain critical activities, an improvement of 16.12% can be achieved, thus reducing the duration of the stage by 2 days.